1974
DOI: 10.2307/1959742
|View full text |Cite
|
Sign up to set email alerts
|

The Divisive Primary Revisited: Party Activists in Iowa

Abstract: This study was conducted to test the frequently made assertion that primary elections are divisive among party activists who participate in primary and subsequent general election campaigns. Analysis of data collected from 209 campaign workers personally identified by five candidates in two vigorously contested races for Congress in Iowa's First District indicated that the activists were an elite group on whom the primary had a divisive impact that was particularly notable among those who supported candidates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
0

Year Published

1979
1979
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(37 citation statements)
references
References 8 publications
1
36
0
Order By: Relevance
“…This research shows that supporters of losing candidates were less active on behalf of the party nominee than supporters of the winning candidate (Johnson and Gibson 1974;Comer 1976;Stone 1984;1986;Southwell 1986;Buell 1986). This negative carryover effect is consistent with the divisive nomination hypothesis.…”
Section: Theoretical Frameworkmentioning
confidence: 82%
“…This research shows that supporters of losing candidates were less active on behalf of the party nominee than supporters of the winning candidate (Johnson and Gibson 1974;Comer 1976;Stone 1984;1986;Southwell 1986;Buell 1986). This negative carryover effect is consistent with the divisive nomination hypothesis.…”
Section: Theoretical Frameworkmentioning
confidence: 82%
“…While this hypothesis is appealing, countervailing evidence calls it into question. Other members also touched by scandal-Diggs of Michigan, Flood of Pennsylvania, and Patten of New Jersey as examples-all survived both primary battles and general election contests against candidates who should have been able to unify the opposition (see Johnson and Gibson, 1974;Hacker, 1965). Table 3 also reveals that 14 of the 19 who beat incumbents won primary campaigns to gain their party's nomination.…”
Section: New Members Defeating Incumbentsmentioning
confidence: 99%
“…To date, only one of these potential explanations has been put to the empirical test. Johnson and Gibson (1974) found that divisiveness did produce a loss of campaign workers in November. Using survey data collected in 1972 and 1976, a second explanation will be confirmed here: that supporters of losing contenders are more likely to defect in general elections.…”
Section: Divisive Primaries and Defection In General Electionsmentioning
confidence: 99%